Penerapan Pendekatan Saintifik Untuk Meningkatkan Kemampuan Membaca Al Qur’an Dengan Metode Pembiasaan Tadarus Al Qur’an Pada Diri Peserta Didik TPQ Nurul Islam Desa Soka, Poncowarno, Kebumen - Wi Hargina, Devi Yaniar; Tamrin, Khusni; Wijinurrokhmah, Wijinurrokhmah; Fatimah, Siti; Rinawati, Atim (IAINU Kebumen, 2022)
This research is motivated by the importance of the Qur'an for human life, therefore it is very necessary to read and write the Qur'an especially for children. The purpose of this study is to improve the ability to read the Koran in students so that students are accustomed to reading the Quran and also increase the ability to improve understanding in accordance with the science of recitation. While in this study using a scientific approach at TPQ Nurul Islam. Then the type of research used in this research is classroom action research, with the research subjects being students of TPQ Nurul Islam Soka Poncowarno Village. Data collection techniques were carried out by interview, observation, and documentation. The validity of the data by using trigulation. So that in this study, data were obtained that students were fluent in reading the Koran with the tadarus al Quran habituation method and how to read it according to the science of recitation. Then by using the knowledge test, data were obtained that students who could understand the science of recitation were 66.67%, while those who did not understand were 33.33%.